NCI in vitro and in silico anticancer screen, cell cycle pertubation and apoptosis-inducing potential of new acylated, benzylidene and isopropylidene derivatives of andrographolide - Wong, Charng Choon; Sagineedu, Sreenivasa Rao; Sumon, Shariful Hasan; Mohamad Sidik, Shiran; Phillips, Roger; Lajis, Nordin; Stanslas, Johnson (Elsevier, 2014)
Andrographolide (AGP) is the main bioactive constituent isolated from the traditional medicinal, Andrographis paniculata which contributes towards its various biological activities, including anticancer property. In this study, a series of new AGP derivatives were semi-synthesised and screened against the NCI in vitro 60 cell lines. From the screening results, we had identified SRS07 as the most potent AGP derivative, against breast and colon cancer cell lines. Subsequently, SRS07 was tested for its capability to induce cell cycle arrest and apoptosis in MCF-7 and HCT116 cancer cells. SRS07 effectively induced G1 cell cycle arrest in both cell lines and ultimately apoptosis by inducing DNA fragmentation in HCT116 cells. The apoptotic cell death induced by SRS07 was confirmed via FITC Annexin-V double staining. Western blot analysis of SRS07-treated HCT116 cells revealed that the compound induced apoptosis be activating caspase 8 which in turn cleaved Bid to t-Bid to initiate cell death cascade. Prediction of the possible mode of action of SRS07 by utilising NCI COMPARE analysis failed to reveal a distinct mechanism category. Hence, it is speculated that SRS07 possesses novel mechanism of action. In conclusion, SRS07 demonstrated superior in vitro anticancer profiles and emerged as a potential lead anticancer candidate.